Retromer terminates the generation of cAMP by internalized PTH-receptors - Feinstein, Timothy N. (2011)
Generation of cAMP by G protein–coupled receptors (GPCRs) and its termination is currently thought to occur exclusively at the plasma membrane of cells. Under existing models of receptor regulation, this signal is primarily restricted by desensitizationof the receptors through their binding to β-arrestins. However, this paradigm is not consistent with recent observations that the parathyroid hormone receptor type 1 (PTHR) continues to stimulate cAMP production even after receptor internalization, as β-arrestins are known to rapidly bind and internalize activated PTHR. Here we show that β-arrestin1 binding prolongs rather than terminates cAMP generation by PTHR, and that cAMP generation correlates with the persistence of arrestin-receptor complexes on endosomes. We found that PTHR signaling is instead turned-off by the retromer complex, which regulates traffic of internalized receptor from endosomes to the Golgi apparatus. Thus, binding by the retromer complex regulates sustained cAMP generation triggered by an internalized GPCR.